PATHOPHYSCHOLOGICAL FEATURES OF STRESS-RELATED DISORDERS IN COMBATANTS - Sukharieva, Viktoriia; Kozhyna, Hanna; Chernenko, Inna; Lytvynenko, Vasyl (Eastern Ukrainian Medical Journal, 2025)
Introduction. During active hostilities, the issue of mental health in our society becomes very acute. The study of the mental health of military personnel participating in the war is particularly relevant. The purpose of the study was to investigate the psychopathological symptoms of disorders specifically related to the stress of war in combatants who were treated in different hospital departments.Methods. The study included 242 servicemen of the Armed Forces of Ukraine who were receiving treatment in different hospital departments. Psychodiagnostic assessment was conducted using the GAD-7, PHQ-9, PCL-5, PSS-SR questionnaires, and the DERS scale.Results. During the psychodiagnostics examination of servicemen treated in the hospital, anxiety-depressive syndrome was significantly more common in patients of the surgical unit, and post-communication syndrome in patients of the neurological unit. Adaptation disorder was found in almost a third of patients in all three departments. PTSD, anxiety disorder, personality and behavioral disorders were detected equally frequently in patients from different hospital departments. An analysis of the relationships between symptoms showed that anxiety-insomnia, post-traumatic and socially maladaptive syndromes were typical for servicemen treated in the therapeutic department, for patients in the neurological department – avoidant, depressive-anxious and insomnia-social syndromes, and for patients in the surgical department – acute traumatic, anxious-depressive and obsessive-avoidant syndromes.Conclusions. The identified peculiarities of symptoms and syndromes in patients of the therapeutic, neurological and surgical departments indicate the need for a differentiated approach to providing psychological assistance to servicemen undergoing treatment in a hospital, considering their underlying disease.The special vulnerability of neurological patients to the development of more severe psycho-emotional disorders is of great practical importance, as it indicates the need to develop specific protocols for psychological support for servicemen with neurological injuries.